Pengaruh Hedonic Shopping Motivation, Price Discount dan Sales Promotion terhadap Impulsive Buying pada Produk Fashion Jiniso di Tiktok Shop (Studi pada Konsumen Generasi Z di Kota Tangerang) - Irawan, Marsella Hamda; Abdul Rauf (BUDGETING : Journal of Business, Management and Accounting, 2025)
TikTok launched the TikTok Shop feature in order to make it easier for consumers to shop without the need to switch applications. This study aims to determine the effect of hedonic shopping motivation, price discount, and sales promotion on impulsive buying of Jiniso fashion products. This study uses a quantitative approach to the population, namely Generation Z in Tangerang City. The sampling technique used is non probability sampling with a purposive sampling approach. The sample used amounted to 100 respondents. The results of this study indicate that partially the variables of hedonic shopping motivation, price discount, and sales promotion have a positive and significant effect on impulsive buying. In simultaneous research (together), hedonic shopping motivation, price discount, and sales promotion have a positive and significant effect on impulsive buying. The coefficient of determination test results were obtained from the Adjusted R-Square value of 0.947 or 94.7%. This shows that the variables hedonic shopping motivation (X1), price discount (X2), and sales promotion (X3) affect impulsive buying (Y) by 94.7%, and the remaining 5.3% is influenced by other variables not examined in this study. The novelty of this research is that there is no previous research that examines in full that hedonic shopping motivation, price discount, and sales promotion are important factors that can shape impulsive buying. This research broadens insights into the factors that trigger impulsive purchases in online shopping and provides recommendations for the fashion industry in designing more effective marketing strategies in order to increase consumer attractiveness and engagement, resulting in increased sales through TikTok Shop.   Keywords: Hedonic Shopping Motivation, Impulsive Buying, Price Discount, Sales Promotion.